Porous sulfide scaffolded solvent-free PEG-Ti hybrid polymer: All-solution-processed thin film composite polymer electrolytes directly on electrodes for lithium-ion batteries. (September 2019) - Cai, Ting-Jhen; Lo, Yi-Hsuan; Wu, Jih-Jen
Abstract: In this work, thin solid-state electrolyte films composed of porous sulfide film scaffolding solvent-free polyethylene glycol-titanium (PEG-Ti) hybrid polymer electrolyte are directly constructed on the electrodes using a pressing-free all-solution-processed route. Porous Li7 P3 S11 (LPS) thin films are deposited on the electrodes using doctor blade method with the LPS slurry in which LPS powders are prepared by solution process as well. The porous LPS thin films are further employed as the scaffolds for the infiltration of PEG-Ti hybrid polymer electrolytes to construct the Li-ion composite electrolytes on electrodes. A Li ion conductivity of 1.6 × 10 −4 Scm −1 at 25 °C is achieved in the optimized porous LPS-scaffolded solvent-free PEG-Ti composite polymer electrolyte, which is 3-fold enhanced in comparison with the solvent-free PEG-Ti hybrid polymer electrolyte. Graphical abstract: Image 1 Highlights: All-solution-processed thin film electrolyte directly on electrode is reported. A porous LPS scaffold is deposited on the electrode using doctor blade method. PEG-Ti hybrid polymer electrolyte is infiltrated into the LPS scaffold. Porous LPS-scaffolded solvent-free PEG-Ti composite polymer electrolyte is formed. A Li ion conductivity of 1.6 × 10-4 Scm-1 at RT is achieved in the electrolyte.